Physical activity, night eating, and mood state profiles of athletes during the COVID-19 pandemic - Turgut, Mine; Soylu, Yusuf; Metin, Serkan Necati (Progress in Nutrition, 2020)
Study Objectives: The aim of this study was to examine the effect of COVID-19 Pandemic physical activity, night eating, and mood in athletes. Methods: 278 (men: 167 and women: 111) athletes from different branches participated the research voluntarily. In the research, personal information form and IPAQ-SF to measure the level of physical activity, the Night Eating Scale (NE) to measure the night eating level, and the Brunel Mood Scale for the mood were used. In the analysis of the data, arithmetic mean, standard deviation, correlation, and regression analysis were used. Results: According to the research findings, a negative significant and high correlation was found between IPAQ high intensity and IPAQ total energy expenditure and fatigue mood. There was a positive and high relation between night eating and mood swings of fatigue, depression, and angry. It was determined that eating at night did not predict physical activity, and eating at night predicted vigorous mood by 21%. Conclusion: According to the results of the study, it was observed that during the COVID-19 pandemic, athletes could remain physically active, but because of the negative effects of staying home in daily life, it had negative effects on night-time eating behaviour and mood.